Role of Topical Flavonoids as Antioxidants to Preserve Healthy Skin – A Review - Jain, Mrs. Saloni (Asian Journal of Pharmaceutics (AJP), 2022)
As a result of the negative effect of some of the horny extract’s associated proteins, the skin is continuously exposed to numerous environmental factors, particularly pollution as well as ultraviolet radiation (UV). As a result, the horny isolate can be adversely affected by the toxic influence of many of its associated proteins. The immediate absorption of UV light through the use of epithelial chromophores, the creation of excited states as well as the subsequent chemical changes, or even photosensitization processes, wherein UV light is absorbed by excited photosensitizer and their responses encourage the production of reactive oxygen species, are all processes that are involved in the environmental pollutants advanced by UV light. Polluting chemicals’ actions are not completely understood, but evidence suggests that one of the key processes involved is oxidative stress caused by lipid peroxidation, which has the potential to cause harm to sebum content, stratum corneum integrity, and skin ageing. Numerous studies have indicated the effectiveness of natural antioxidants, with a focus on natural substances, in promoting the preservation of the skin’s physiological equilibrium.